EFFECT OF GENDER EMPOWERMENT IN AGRICULTURE ON FOOD SECURITY OF FARMING HOUSEHOLDS IN OGUN STATE, NIGERIA - Ogunnaike, M. G.; Shittu, A. M.; Kehinde, M. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
Women play an important role in agricultural growth in developing countries, but they face persistent obstacles and economic constraints limiting further inclusion in agriculture. The Women’s Empowerment in Agriculture Index (WEAI) measures the empowerment and inclusion of women in the agriculture sector and can also be used more generally to assess the state of empowerment and gender parity in agriculture and to identify key areas in which empowerment needs to be strengthened. The study adopted the abbreviated version of the WEAI (A-WEAI) and documented the effect of Women empowerment on food security in Ogun state, Nigeria. Primary data were collected using multi-stage random sampling technique from a cross section of 206 farming households during the 2016 production season in Ogun State. Data were analysed using descriptive statistics and the A-WEAI model. The food security score was generated using the USDA approach While Ordered Probit was used to assess the effect of women empowerment on household food security. Households were classified as having high food security (5.7%), marginal food security (17.6%), low food security (35.8%) and very low food security (40.9%). The Ordered Probit model as specified revealed that gender (p<0.05), middle age group (p<0.10), work achievement (p<0.10) and empowerment (p<0.10) significantly improve the food security status of farming household in the study area. This study therefore recommends that efforts should be made through gender empowerment of men and women to improve farming households’ food security status in order to achieve the sustainable development goals.